Performance of a Low Energy Ion Source with Carbon Nanotube Electron Emitters under the Influence of Various Operating Gases - Zhang, Huzhong (Nanomaterials (Basel), 2020)
Low energy ion measurements in the vicinity of a comet have provided us with important information about the planet’s evolution. The calibration of instruments for thermal ions in the laboratory plays a crucial role when analysing data from in-situ measurements in space. A new low energy ion source based on carbon nanotube electron emitters was developed for calibrating the ion-mode of mass spectrometers or other ion detectors. The electron field emission (FE) properties of carbon nanotubes (CNTs) for H(2), He, Ar, O(2), and CO(2) gases were tested in the experiments. H(2), He, Ar, and CO(2) adsorbates could change the FE temporarily at pressures from10(−6) Pa to10(−4) Pa. The FE of CNT remains stable in Ar and increases in H(2), but degrades in He, O(2), and CO(2). All gas adsorbates lead to temporary degradation after working for prolonged periods. The ion current of the ion source is measured by using a Faraday cup and the sensitivity is derived from this measurement. The ion currents for the different gases were around 10 pA (corresponding to 200 ions/cm(3) s) and an energy of ~28 eV could be observed.